Surpassing the Boundaries of Fortitude: A Study on Psychological Resilience Theory in "Fatal Forecast" by Tougias - Keleş, Aybike (Cagatay Sarp, 2025)
Every individual experiences traumatic events, including illness, death, and natural disasters, at some point in their lifetime. Although some individuals endeavor to resist the challenges that life presents, others succumb to these challenges, believing that they will ultimately fail. The capacity to persevere in the face of adversity is, in this context, known as psychological resilience. In Michael Tougias's Fatal Forecast, the protagonist Ernie seeks solutions to the challenges he faces, rather than surrendering to them. He overcomes the problems he faces on his sea cruise by using problem-solving and self-regulation abilities, as well as, most significantly, accepting the calamity that befell him. Ernie's capacity to control his urges is also one of the key elements in sustaining both his spiritual and physical endurance. Ernie's psychological resilience functions as a protective barrier, shielding him from the adverse effects of turbulent waves, hunger, and severe weather. When these factors, together with Ernie's capacity to adapt to environmental situations, overcome obstacles using his power, and inner strength, are examined, he fits the criteria for being a resilient person. The aim of the study is to determine whether psychological resilience is an inherent trait or the result of an individual's perseverance and fortitude in the face of adversity, as illustrated by the character Ernie. The aim of this paper is to examine the importance of resilience theory through the story of character Ernie.
Keywords: British and Irish Language, Literature and Culture; Psycological Resilience; Challange; Perseverance; adversity; Psikolojik SAĞLAMLILIK; Mücadele; Dirayet; Engeller; İngiliz ve İrlanda Dili, Edebiyatı ve Kültürü